Dampak alokasi dana perimbangan (DAU, DAK, DBH) terhadap tingkat ketimpangan antar daerah di Provinsi Jambi Periode 2010-2019 - Sidik, Muhamad; Hidayat, Syurya; Ridwansyah, Muhammad (Jurnal Paradigma Ekonomika, 2020)
This study aims to analyze 1) How is the development of the allocation of balancing funds (DAU, DAK, and DBH) in Jambi Province 2) What is the condition of the level of inequality between regions in Jambi Province 3) How does the allocation of balancing funds (DAU, DAK, and DBH) affect the level of inequality between regions in Jambi Province. The analysis used is a descriptive quantitative analysis and uses secondary data. From the results of this study, it was found that the development of the allocation of Balancing Funds (DAU, DAK, and DBH) in Jambi Province tends to increase. The development of the level of inequality between regions in Jambi Province tends to decline. The average value of Williamson Index Jambi Province in 2010-2019 is 0.47, so it can be concluded that the level of inequality between regions in Jambi Province is in the medium category. DAU and DAK have a significant effect on the level of inequality between regions in Jambi Province, while DBH does not have a significant effect on the level of inequality between regions in Jambi Province.